Some aspects of the reproductive biology of roughear scad, Decapterus tabl (Berry, 1968). - Balunan, Rielyn Losaria
Roughear scad, Decapterus tabl which is one of the species that belongs to the genus Decapterus, is important for fisheries in the Philippines. Meristic counts of 4 Decapterus tabl were recorded and measured for correct identification of the species. No literatures about the reproductive biology of this species had been reported, thus, this study will be the first report in the Philippines. A total of 235 fish samples (54 ovaries) were examined to assess the reproductive biology of Decapterus tabl caught by surrounding nets that operate and landed in Miagao, Iloilo during the months of February to April, 2015. For the Length-Weight relationship, values of exponent b showed a positive allometric growth which arranged from 3.241 to 3.4807 whiles values of r2 were <0.90. as the girth increases, the length also increases. Size at first maturity for the gonadosomatic index vs. length was estimated to be 152.1mm fork length at 50% maturity was estimated to be 183.84 mm fork length. Female gonads were classified into five maturity stages based on histological data from the maturity stages of Yamaguchi et.al (2006): (1) immature/resting stage; (2) developing stage; (3) maturing stage; (4) ripe/spawning stage; (5) spent stage. Female D. tabl were proved to be asynchronous spawners, meaning that they spawn more than once in a single spawning season because postovulatory follicles exist at the same time with yolk stage oocytes in histological sections of ovaries. All parameters estimated from this study will be useful for stock assessment of Decapterus tabl in the Philippines and will contribute to the management and conservation of this species into sustainable yield.